Identification of the association between rs41274221 polymorphism in the seed sequence of microRNA‐25 and the risk of neonate sepsis. Issue 9 (21st January 2019) - Zheng, Ge; Xiang, Wenna; Pan, Minli; Huang, Yihua; Li, Zhishu
Abstract: Background: Many studies have investigated the role of microRNA‐25 (miR‐25) in the initiation and progression of sepsis in newborns. In this study, we aim to explore how rs41274221 polymorphism in miR‐25 compromises the interaction between miR‐25 and CD69, so as to understand the mechanisms involved in the control of sepsis in newborns. Methods: Computational analysis, luciferase assay, real‐time polymerase chain reaction (PCR), and western blot analysis were performed in this study. Results: The luciferase assays results showed that CD69 was a target gene of miR‐25, because the luciferase activity in cells transfected with wild type CD69 was much lower than that in the cells transfected with mutant CD69 or the scramble control. Real‐time PCR and western blot analysis results showed that the expression of miR‐25 in sepsis patients was significantly upregulated as compared with that in the normal control group, and the CD69 position ratio as well as the messenger RNA (mRNA) and protein level of CD69 in sepsis patients was much higher than those in the normal control group. As compared with the scramble control, miR‐25 mimics, and CD69 small interfering RNA (siRNA) downregulated the mRNA and protein expression of CD69, whereas the expression of CD69 mRNA and protein in cells transfected with miR‐25 inhibitors was significantly higher as compared with that in the scramble control. In addition, interferonγ production was significantly downregulated in cells transfected with miR‐25 inhibitors but notably upregulated in cells transfected with miR‐25 mimics or CD69 siRNA. Conclusion: The single‐nucleotide polymorphism (SNP; rs41274221) in miR‐25 is associated with the risk of sepsis in newborns. Abstract : Many studies have investigated the role of microRNA‐25 (miR‐25) in the initiation and progression of sepsis in newborns. In this study, we aim to explore how rs41274221 polymorphism in miR‐25 compromises the interaction between miR‐25 and CD69, so as to understand the mechanisms involved in the control of sepsis in newborns. The results from this study demonstrated that the presence of rs41274221 polymorphism is associated with the risk of neonate sepsis, and rs41274221 may function as a potential biomarker for the risk of sepsis in neonates.